Improving Customer Engagement with Digital Gift Features in Mobile Banking Using Design Thinking Stages - Heru Kurniawan; Hadziq Fabroyir (Jurnal Indonesia Sosial Teknologi, 2024)
Among the challenges faced by conventional banks is the provision of banking services that can compete with digital banks. Mobile banking is one of the banking services in the form of an application that can be a tool to compete through the development of relevant, attractive, and effective features or services to meet customer needs. People have a habit of giving gifts to each other adopting the value of the spirit of giving in social life, especially at special moments. Digital gifts are a new trend to be able to send gifts to each other without the need to meet face-to-face. The development of digital gift services in mobile banking is the result of observing customer needs using the Design Thinking stage to obtain solutions to these problems. The addition of gamification elements to the development of digital gift services is expected to increase customer engagement and increase customer retention. The data collection method is in the form of a survey of customers. This research is a qualitative research that describes the needs of customers for digital gift services. This research was conducted from January to May 2024. The respondents of this study are customers who have been actively using mobile banking.